ANALISIS BAHAYA PADA AKTIVITAS PEKERJA KETINGGIAN PEMASANGAN KABEL INTERNET FIBER TO THE HOME - Dermawan, Dedy; Sumantika, Arsyad (Computer Science and Industrial Engineering, 2023)
Fiber to the Home (FTTH) is becoming more and more popular since it can offer a dependable and quick internet connection. Because they are frequently at a height, the field technician's cabling process calls for both physical and mental fortitude. In this study, the JSA approach was used to identify workplace hazards and suggest preventative strategies to reduce the risk of accidents and other negative work-related outcomes. There are 24 sources of danger listed at a very high level, making the first level of risk very high. Activities that cause hazards must be suspended until the risks may be reduced, according to the AS/NZS 4360:2004 standard semi-quantitative risk assessment guide. Priority 1 is the second degree of risk. Priority level 1 sources of danger include 10 different sources. Controlling it as quickly as feasible is the step that needs to be taken. There are four sources of risk that are categorized as considerable, the third risk level. The necessary course of action is to demand technical advancements. The third priority is the fourth danger level. At priority level 3, there are three sources of risk indicated. The actions that need to be conducted need to be closely watched and supervised. There are 11 sources of risk that are included in the fifth level of risk, which is tolerable.